Religious Geography and County-Level Sex Ratios in China - Tong, Yunping ca. 20./21. Jh. (Journal for the scientific study of religion, 2021)
The sex ratio at birth in China is highly imbalanced in favor of boys. Past research on sex ratios in China emphasizes economic factors for their weakening effect on the Confucian tradition of son preference. Research in the sociology of religion suggests that religious geography may affect sex ratios through the spill-over of religious teachings to those living in areas dominated by a religious tradition. To assess this linkage, we investigate the relationship between religious geography and county-level child sex ratios using the 2000 China Population Census and the 2004 China Economic Census, the most complete and recent data available on religious presence in China. Applying spatial analyses of 2,685 counties (over 90% of all counties), we find that counties with a greater presence of Daoist temples have more imbalanced (male-biased) sex ratios, whereas a greater presence of Buddhist temples and Islamic mosques is associated with less imbalanced sex ratios.